Rancang Bangun Alat Pemantau Dan Kontrol Kondisi Ruangan Green House Untuk Budidaya Tanaman Stroberi Berbasis Internet Of Things (IoT) - Tarigan, Jonshon; Albert Zicko Johannes; Martelda Natbais; Ari Bangkit Sanjaya Umbu (Politeknik Caltex Riau, 2023)
Strawberries are horticultural crops that can grow well in subtropical regions. Strawberries require cool environmental conditions with temperatures between 17°C-20°C and humidity between 80% -90%. Cultivating strawberries in the tropics is a challenge in itself because of the temperature and humidity in this area. One way to cultivate strawberry plants in the tropics is to use a Green House. Green House is designed to maintain the temperature and humidity according to the needs of the strawberry plants. This study aims to create a system monitoring and controlling greenhouses using the internet of things. Users can monitor and control the condition of the Green House via an Android smartphone with the Blynk application. When the air temperature and humidity values are in the Green House, the system will work to readjust the temperature and humidity in the Green House. This system uses ESP32 as the control center and a DHT22 sensor to measure air temperature and humidity. Based on the results of the design and performance analysis of the tool, the accuracy of the air temperature gauge is 99.52% and the air humidity is 99.29%. The system successfully controlled the temperature and humidity in the Green House room for 23 days of testing.